1988
DOI: 10.1089/jop.1988.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Alpha1-Adrenoceptors in the Albino Rabbit Ciliary Process

Abstract: H-Prazosin and^H-rauwolscine binding sites were identified in a membrane suspension prepared from albino rabbit iris + ciliary body. Scatchard analysis of saturation binding experiments demonstrated that both %-prazosin and %-rauwolscine bind to a single population of binding sites with Krj values of 0.87 nM and 5.33 nM, respectively. Bmax values of 65.7 and 198 fmol/mg protein were obtained for^H -prazosin and 3jj-rauwolscine, respectively. Displacement studies by several adrenergic agonists and antagonists i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Together, our findings provide a better understanding of the ciliary body physiology, completing a preclinical translational research addressed to combat glaucoma. Remarkably, a therapeutic strategy resulting from combining melatonin, sold as a supplement and lacking collateral effects even at high doses in the eye (Rosenstein et al, 2010;Sanchez-Barcelo, Mediavilla, Tan, & Reiter, 2010), and prazosin, approved for the therapy of blood hypertension (Brogden et al, 1977;Mallorga, Buisson, & Sugrue, 1988;Singleton et al, 1989;Torvik & Madsbu, 1986), could readily enter into clinical trials to assay for safety and efficacy in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our findings provide a better understanding of the ciliary body physiology, completing a preclinical translational research addressed to combat glaucoma. Remarkably, a therapeutic strategy resulting from combining melatonin, sold as a supplement and lacking collateral effects even at high doses in the eye (Rosenstein et al, 2010;Sanchez-Barcelo, Mediavilla, Tan, & Reiter, 2010), and prazosin, approved for the therapy of blood hypertension (Brogden et al, 1977;Mallorga, Buisson, & Sugrue, 1988;Singleton et al, 1989;Torvik & Madsbu, 1986), could readily enter into clinical trials to assay for safety and efficacy in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our findings provide a better understanding of the ciliary body physiology, completing a preclinical translational research addressed to combat glaucoma. Remarkably, a therapeutic strategy resulting from combining melatonin, sold as a supplement and lacking collateral effects even at high doses in the eye (Rosenstein et al, ; Sánchez‐Barceló, Mediavilla, Tan, & Reiter, ), and prazosin, approved for the therapy of blood hypertension (Brogden et al, ; Mallorga, Buisson, & Sugrue, ; Singleton et al, ; Torvik & Madsbu, ), could readily enter into clinical trials to assay for safety and efficacy in humans with ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A number of closely related subtypes of the α 1 subfamily (α 1A , α 1B , α 1C and α 1D ) and the α 2 subfamily (α 2A/D , α 2B and α 2C ) have been identified on the basis of their sequence homology, pharmacological profile and signal transduction mechanisms (Watson & Arkinstall, 1994; MacKinnon et al 1994). Both subfamilies of α‐AR have been identified on the rabbit CBE (Mallorga et al 1988; Jin et al 1994) and more recent studies have suggested that in rabbit CBE α 1 ‐ARs are localized on the PCE cells, whilst α 2 ‐ARs, specifically α 2A ‐ARs, are localized to the NPE cells (Schutte et al 1996; Suzuki et al 1997). Our studies are consistent with these findings in that the phenylephrine‐mediated increase in I K(Ca) is mediated via an α 1 ‐receptor subtype in rabbit PCE cells.…”
Section: Discussionmentioning
confidence: 99%